PELAKSANAAN PROGRAM PEMAGANGAN PADA SEKOLAH TINGGI PARIWISATA BALI INTERNASIONAL DI LUAR WILAYAH INDONESIA - I Gusti Ngurah Wira Wedawitry Wedasteraputra Suyasa; Luh Merry Dyanthi (Universitas Mahendradatta, 2025)
The eligibility and achievement standards for participants participating ininternships outside Indonesia are tailored to the goals of the internship organizer. Thescope of internship achievements is usually tailored to the circumstances of thecompany hosting the internship. Broadly speaking, internships aim to developindividual competencies, apply theoretical concepts to actual work practices, developsoft skills, especially communication and interpersonal relationships, and foster theability to solve problems independently, make decisions, and be accountable for them.